map f [x1, x2, ..., xn] == [f x1, f x2, ..., f xn] map f [x1, x2, ...] == [f x1, f x2, ...]
>>> map (+1) [1, 2, 3] [2,3,4]
map id = cat map (g . f) = map f >-> map g
toNonEmpty (map f xs) = map f (toNonEmpty xs)
map f [x1, x2, ..., xn] == [f x1, f x2, ..., f xn] map f [x1, x2, ...] == [f x1, f x2, ...]this means that map id == id
>>> map (+1) [1, 2, 3] [2,3,4]
>>> map id [1, 2, 3] [1,2,3]
>>> map (\n -> 3 * n + 1) [1, 2, 3] [4,7,10]
>>> S.stdoutLn $ S.map reverse $ each (words "alpha beta") ahpla ateb